EKSPLORASI PEMAHAMAN LITERASI MEMBACA TEKS NARASI PADA PESERTA DIDIK SEKOLAH DASAR - Shella Salsabila; Eko Kuntarto; Silvina Noviyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine and describe the literacy understanding of reading narrative texts of elementary school students in understanding information and reflecting on information. This research was conducted at SD Negeri 132 Jambi City from July to August 2024. The research data were collected by means of observation, interviews, documentation, and tests. After the data were collected, the data were analysed quantitatively. The results showed that the literacy comprehension of reading narrative texts of grade III students of SD Negeri 132 Jambi City through understanding information in this study, based on qualifications was quite good. This is because the percentage of students who obtained a score of 10 (very good) and a score of 8 (good) totalled 69.56%. The literacy comprehension of reading narrative text of third grade students of SD Negeri 132 Jambi City through reflecting information in this study, based on qualifications is good. This is because the percentage of students who obtained a score of 5 (very good) and a score of 3 (good enough) totalled 82.61%. Factors inhibiting the understanding of reading literacy of students of SD Negeri 132 Jambi City are from the students themselves (lack of interest in reading), from schools (libraries that are less comfortable), and from parents (lack of attention). From the results of this study to principals and teachers it is recommended that they always actively intensify activities aimed at increasing students' reading literacy. Teacher assistance is needed in reading corner activities to give maximum impact on students' interest in reading. Joint literacy activities should always be scheduled, and if the weather is rainy the location can be moved to the school library. School principals need to make the library neater and more comfortable and equipped with a wider range of non-academic reading books so that reading literacy-related activities can use the library. As well as being an alternative location for students to spend their break time.